Application of the Sea Approach (Starter Experiment Approach) in Practicum Activities to Improve Academic Skills Students' in Biology Lessons At SMA Negeri 1 Banyuwangi - Santi, Triana Kartika; Hermawan, Candra; Widyana, Yulia Ayu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The results of preliminary observations on Biology practicum learning at SMA Negeri 1 Banyuwangi show that 80% of students have(academic skills academic skills) below 75. Based on these problems, efforts need to be made to improve(academic skills academic skills).Â  students in biology practicum at SMA Negeri 1 Banyuwangi. This can be done by applying the SEA approach (Starter Experiment Approach). This research is a type of classroom action research conducted in two cycles. In general, the flow of the implementation of classroom research includes the stages of action planning, implementation of actions, observation and reflection of actions. From the research results, it is known that practicum learning by applying the SEA (Starter Experiment Approach Approach)can improve(academic skills academic skills students') in biology practicum at SMA Negeri 1 Banyuwangi. There was an increase in the number of students who obtained practicum scores above 75 from the first cycle to the second cycle, where in the first cycle there were 78% of students who obtained above 75 and increased in the second cycle to 82%. This shows that learning SEA (Starter Experiment Approach)Â  has a real impact on increasing student scores in terms of academic skills in learning biology practicum at SMA Negeri 1 Banyuwangi.